THE INFLUENCE OF NaCl SOLUTION FLOW RATE ON ION ABSORPTION OF CAPACITIVE ELECTRIC CARBON PLATE - Ellys Kumala Pramartaningthyas (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2021)
Research on desalination technology in seawater is being developed. This is because sea water has not been used optimally to meet community needs. One of the rapidly developing desalination systems is desalination technology using a capacitive carbon plate. The development of this desalination system technology is carried out using electrode plates made of carbon. These plates are capable of absorbing salt ions through the porous surface. The amount of ion absorbed is determined by the pore surface structure of the plate, the salt flow rate, the number of plates used, the applied voltage and other factors. The salt flow rate between the carbon plates determines the speed of the salt ions to reach the smallest pores on each plate surface. For this reason, this article has conducted research by testing the variation in the flow rate of NaCl solution to the amount of salt ions absorbed on the carbon plate.